EFEKTIVITAS PENGGUNAAN MEDIA GAMBAR TERHADAP PENINGKATAN KEMAMPUAN MENULIS DESKRIPSI - Rima Nur'aeni; Iis Ristiani (Universitas Negeri Makassar, 2026)
This study aimed to measure the effectiveness of using visual media to improve the descriptive writing skills of fifth-grade students at Selahuni State Elementary School. This study used a quantitative approach with a quasi-experimental method and a non-equivalent control group design. Two groups were involved: an experimental class that received visual media treatment and a control class that learned using conventional methods. Data were collected through a writing test. The research instrument consisted of descriptive writing prompts. Data analysis was conducted by calculating pretest-posttest scores, gain scores, and t-tests to determine the significant differences between groups. The results showed a greater increase in descriptive writing skills in the experimental class than in the control class. Visual media has been proven to increase students' motivation, focus, and creativity in writing activities. Thus, visual media can be declared effective as a supporting tool for learning descriptive writing among elementary school students.